2019
DOI: 10.1186/s12879-019-4175-0
|View full text |Cite
|
Sign up to set email alerts
|

Low concordance of oral and genital HPV infection among male patients with sexually transmitted infections in Vietnam

Abstract: Background Human papillomavirus (HPV) causes cancers in men, including penile, anal, and oropharyngeal cancers. This cross-sectional study aimed to investigate the prevalence, the genotypes, and the risk factors of HPV infections in the oral cavity, compared to those in the genitals, among males diagnosed with sexually transmitted infections (STIs) in Vietnam. Methods Oral, urinary, penile, and urethral samples were collected from 198 male Vietnamese patients with STIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The prevalence of high-risk anal HPV infection observed in this survey of MSM is comparable to the prevalence rates reported previously in Vietnam (Le et al, 2019, Vu et al, 2013, although we did find higher high-risk anal HPV infections in HCMC than in Hanoi. Higher HPV prevalence was also observed in a previous study of male sex worker where the prevalence was highest in Ho Chi Minh City (59%), followed by Hanoi (19%) and Nha Trang (6%) (Vu et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of high-risk anal HPV infection observed in this survey of MSM is comparable to the prevalence rates reported previously in Vietnam (Le et al, 2019, Vu et al, 2013, although we did find higher high-risk anal HPV infections in HCMC than in Hanoi. Higher HPV prevalence was also observed in a previous study of male sex worker where the prevalence was highest in Ho Chi Minh City (59%), followed by Hanoi (19%) and Nha Trang (6%) (Vu et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Information about HPV infection in men was still limited. However, current reports showed that prevalent rate of HPV infection was 25% among male patients with sexually transmitted infections (STIs) and was 23 to 79.6% among patients with penile cancer ( 18 , 19 ). In 2008, the Ministry of Health approved two types of HPV vaccines including Cervarix and Gardasil with the purpose of preventing cervical cancer for girls and young women.…”
Section: Introductionmentioning
confidence: 99%
“…Example of used swabs/brushes include iCleanhcy flocked swabs (Huachenyang Corporation, Shenzhen, China), FLOQSwab R100 and FLOQSwab U80 (Copan Diagnostics Inc., Murrieta, CA, USA) [ 115 , 116 ], and Dacron ® polyester swabs [ 117 ]. Samples can be preserved in transport media like phosphate-buffered saline (PBS) [ 118 ], PreservCyt solution (Hologic Corporation, Marlborough, MA, USA) [ 116 , 119 ], LiquiPrep preservation solution (LGM International Inc., Fort Lauderdale, FL, USA) [ 115 ], and Specimen Transport Medium (Qiagen, Hilden, Germany) [ 117 ]. For the detection of HPV DNA in the head and neck (HNC) region, oral swabs and rinse are commonly kept in saline [ 120 ].…”
Section: Hpv Screeningmentioning
confidence: 99%
“…Commercial kits run on different detection platforms, including the real-time PCR (AmoyDx ® Human Papillomavirus Genotyping Detection Kit from Amoy Diagnostics, Xiamen, China) [ 174 ], gene chip systems (HPV GenoArray Diagnostic Kit from Hybribrio, Chauzhou, China) [ 115 , 156 ], flow cytometric assays (HPV OncoTect ® E6, E7 mRNA Kit, incellDx, CA, USA) [ 176 ], PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) assay [ 53 ], microplate colorimetric hybridization assay (MCHA) [ 115 , 179 ], GenoFlow HPV Array Test Kit (DiagCor Bioscience, Hong Kong) [ 54 ], and Anyplex II HPV28 Detection Kit (Seegene, Seoul, Korea) have been used [ 157 ].…”
Section: Hpv Screeningmentioning
confidence: 99%
See 1 more Smart Citation